Clinical predictors of intra-abdominal lesions in blunt abdominal trauma patients with the conservative treatment - I Gede Parwata; Ketut Wiargitha; Nyoman Golden; Desy Permatasari (Indoscholar, 2019)
Background: Blunt abdominal trauma has a high rate of morbidity and mortality. Assessment of specific clinical symptoms such as abdominal traces, abdominal pain, gross hematuria, pelvic fracture, systolic blood pressure and pulse rate in blunt abdominal trauma patients can predict the presence of intra-abdominal injury, so the use of CT Scan in diagnostics may be selective. The purpose of this study was to determine the predictors of intra-abdominal lesions in patients with blunt abdominal trauma who were treated conservatively. Material and Method: This study used a cross-sectional design. Samples were taken from the medical records, from January 2015 to December 2016. The total sample was 124 patients, were analyzed using Chi-square and logistic regression. This study has passed ethical clearance from the institutional review board of our University Result: The results showed the mean age of patients was 33 years, the majority of patients were male (74.2%), and a negative CT scan was 39.5%. The clinical predictors of intra-abdominal lesions in CT scan of blunt abdominal trauma patients were: abdominal traces (OR: 11.252; 95% CI: 3.257-38.867; p <0.001), abdominal pain with VAS≥5 (OR : 92.968; 95% CI: 14.604-591,837; p <0.001); and gross hematuria (OR: 9.377; 95% CI: 1.539-57.115; p = 0.015). Pelvic fracture, systolic blood pressure, and pulse rate were not statistically proven. Conclusion: Abdominal traces, abdominal pain, and gross hematuria are clinical predictors of intra-abdominal lesions. Predictors should be taken into consideration in decision making to perform an abdominal CT scan in blunt abdominal trauma patients treated conservatively.